A sociological approach to poetry translation modern European poet-translators - Blakesley, Jacob 1978- (Routledge, Taylor & Francis Group, 2020)
Comparing English, French, and Italian poet-translators -- English-language poet-translators -- French-language poet-translators -- Italian-language poet translators -- Three case studies: Tony Harrison, Jacques Ancet, and Maurizio Cucchi
Includes bibliographical references and index
1811
Keywords: Übersetzung; Englisch; Italienisch; Literatur; Französisch; Poetry / Translating; Poetics; Translating and interpreting